STUDI LITERATUR: PENERAPAN MODEL CIRC PADA KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Fitria Tiara Angel; Nidya Chandra Muji Utami; Imaningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low reading comprehension skills of elementary school students so that an effective learning model is needed, one of which is the CIRC model. This research aims to explain the application of the CIRC model on students' reading comprehension skills. This research uses qualitative with PRISMA-based literature study method. The data collection technique was carried out by documenting 25 articles consisting of 10 national articles and 15 international articles, which were obtained through Google Scholar with the Publish or Perish programme. The results explained that the application of the CIRC model can encourage student activeness, understanding the content of reading, finding the main idea, and drawing conclusions. Its success is supported by the role of the teacher, active involvement of students, and appropriate learning media. However, there are some obstacles such as learning environment, emotional, and physiological factors that can be overcome with the right strategy. Based on the results of the study, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) model can improve the reading comprehension skills of elementary school students.